Analisis Keterampilan Berpikir Kritis Siswa SMP Pada Mata Pelajaran IPA Ditinjau Dari Gaya Belajar Visual - Naning Windi Rokayana (Universitas Muhammadiyah Sidoarjo, 2017)
This study aims to analyze the critical thinking skills that have been owned by junior high school students in science subjects in terms of visual learning styles. The identification of critical thinking skills in this study is based on Facione critical thinking indicator ie, interpretation, analysis, inference, evaluation, explanation and self regulation. The subjects of the study in this study consisted of 1 student who has a visual learning style. The research methodology used is qualitative methodology with phenomenology approach. Data collection techniques used are critical thinking skills tests, observation and interviews. data analysis technique used is Miles and Huberman technique. The results of this study suggest that visual subjects are able to resolve science issues with sub skill categories, decode significant,clarity of meaning, examining ideas, query evidence and colectune alternative.